Mechanical and Tribological Properties of Cold-Sprayed Ti Coatings on Ti-6Al-4V Substrates - Khun, Nay Win (2016)
A cold spray process was used to deposit titanium (Ti) coatings of different thicknesses on commercial Ti-6Al-4V (Ti64) substrates. The hardness of the Ti coatings was measured using a Vickers micro-indenter. It was found that the thicker Ti coatings had higher hardness probably due to the better uniformity and higher density of the coatings. The tribological results showed that the friction and wear of the Ti coatings tested against a steel ball under dry condition became lower with higher thickness probably due to the higher wear resistance of the thicker coatings associated with their higher hardness. The specific wear rates of all the Ti coatings were significantly lower than that of the Ti64 substrate as a result of the higher wear resistance of the Ti coatings associated with their cold-worked microstructures and the formation of high wear resistant oxide layers on their wear tracks during the wear testing.